2004
DOI: 10.1136/ard.2003.014175
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid syndrome associated with infections: clinical and microbiological characteristics of 100 patients

Abstract: Objective: To describe and analyse the clinical characteristics of 100 patients with antiphospholipid syndrome (APS) associated with infections. Methods: Patients were identified by a computer assisted search (Medline) of published reports to locate all cases of APS published in English, Spanish, and French from 1983 to 2003. The bilateral Fisher exact test was used for statistics. Results: 59 female and 41 male patients were identified (mean (SD) age, 32 (18) years (range 1 to 78)): 68 had primary APS, 27 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
123
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(128 citation statements)
references
References 73 publications
1
123
2
2
Order By: Relevance
“…Recently, many infections have been emphasized and reported on several occasions to not only potentially trigger the production of these antibodies but also be accompanied by the clinical manifestation of APL itself [14]. Bayoumi et al [15] reported that antiphospholipid syndrome is characterized by the presence of pathogenic autoantibodies against β2 glycoprotein-1 (β2GP1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many infections have been emphasized and reported on several occasions to not only potentially trigger the production of these antibodies but also be accompanied by the clinical manifestation of APL itself [14]. Bayoumi et al [15] reported that antiphospholipid syndrome is characterized by the presence of pathogenic autoantibodies against β2 glycoprotein-1 (β2GP1).…”
Section: Discussionmentioning
confidence: 99%
“…McNeil et al [17] and Asherson et al [18] reported the presence of antiphospholipid antibodies in infectious diseases such as HIV, tuberculosis, measles, chickenpox, hepatitis, parvovirus and rubella. In a study on 100 patients complaining of antiphospholipid syndrome, Cervera R et al [14] found that a urinary tract infection was the associated infection in 10% of these patients. Asherson et al [18] reported that 35% of catastrophic APS cases were preceded by an infection, with urinary tract infections reported to occur in 6% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between LSE and APS was noted in 1985 and additional evidence has been reported that antiphospholipid antibodies are related to the pathogenesis of valvular heart disease [8][9][10]. On the other hand, several studies have suggested the association of APS/LSE and infection [2,11,12]. Cervera et al reported that various infections could be related to thrombotic events in patients with APS, and that catastrophic APS, which is the most severe form of APS, seemed to be triggered mainly by infections [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…One of the triggering conditions of APS is infectious diseases such as skin infections, human immunodeficiency virus infection, pneumonia, hepatitis C virus infections, and urinary tract infections [2]. We describe here a case of a 38-year-old woman with Staphylococcus aureus infective endocarditis (IE) and multiple systemic embolisms.…”
Section: Introductionmentioning
confidence: 99%